Enteroviruses in the early 21st century: new manifestations and challenges. Issue 1 (February 2016) - Lugo, Debra; Krogstad, Paul
Abstract : Purpose of review: Enteroviruses cause a wide variety of diseases with neurologic, respiratory, skin, and gastrointestinal findings. The purpose of this review is to clarify changes in the classification of enteroviruses, provide information about recent disease outbreaks, and to summarize progress toward the treatment and prevention of these infections. Recent findings: Enteroviruses are now classified into four distinct species. New variants of coxsackievirus B1, enterovirus-A71, and enterovirus-D68 (EV-D68) have emerged as causes of recent outbreaks in the United States and other countries, including more severe disease manifestations than previously described. EV-D68 now commonly circulates in the United States, and has been linked to severe respiratory disease and associated with acute flaccid myelitis (AFM). Overcoming enormous political and logistical challenges, fewer than 100 cases of polio have been reported in 2015, and the initiation of 'endgame' strategies appears imminent. Unfortunately, treatment for enterovirus infections remains supportive, although the recently completed pleconaril trial in newborns suggests that antiviral therapy may reduce mortality in neonatal disease. Summary: Clinicians should be aware of the respiratory and neurological manifestations associated with EV-D68 and the potential for severe disease seen with other recently described enterovirus variants. Healthcare professionals should recognize the utility of rapid diagnostic methods and progress toward prevention and treatment of enterovirus infections.